2021
DOI: 10.21203/rs.3.rs-626260/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of COVID-19 among health workers in the Kathmandu valley, Nepal (SEVID-KaV): a longitudinal cohort study

Abstract: Coronavirus Disease 2019 (COVID-19) burden is often underestimated when relying on case-based incidence reports. Seroprevalence studies accurately estimate infectious disease burden by estimating the population that has developed antibodies following an infection. Sero-Epidemiology of COVID-19 in the Kathmandu valley (SEVID-KaV) is a longitudinal survey of hospital-based health workers in the Kathmandu valley. Between December 3-25, we sampled 800 health workers from 20 hospitals and administered a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Another serological study ( 12 ) found that the prevalence of IgG antibody (indication of past infection) to SARS-CoV-2 was 11.4% in East Java, Indonesia. A serological study ( 13 ) among healthcare workers in the Kathmandu valley, Nepal, showed a 23% positivity for polymerase chain reaction (PCR) testing. SARS-CoV-2 seroprevalence study ( 14 ) indicated that a symptom-based PCR-testing strategy missed 62% of COVID-19 diagnoses, and ~36% of individuals with SARS-CoV-2 infection were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another serological study ( 12 ) found that the prevalence of IgG antibody (indication of past infection) to SARS-CoV-2 was 11.4% in East Java, Indonesia. A serological study ( 13 ) among healthcare workers in the Kathmandu valley, Nepal, showed a 23% positivity for polymerase chain reaction (PCR) testing. SARS-CoV-2 seroprevalence study ( 14 ) indicated that a symptom-based PCR-testing strategy missed 62% of COVID-19 diagnoses, and ~36% of individuals with SARS-CoV-2 infection were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Another serological study (12) found that the prevalence of IgG antibody (indication of past infection) to SARS-CoV-2 was 11.4% in East Java, Indonesia. A serological study (13) among healthcare workers in the Kathmandu valley, Nepal, showed a 23% positivity A-G)] where variants sequenced data are available (8). We only show these strains with a maximum percentage > 20%.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal seroprevalence study [20] based on hospital health workers in the Kathmandu valley, Nepal, found that the overall posterior predictive hospital-wise seroprevalence ranged between 38.1% (95% CrI 30.7.0%-44.1%) and 40.5% (95% CrI 34.7%-47.0%). This result suggested that a substantial proportion of health workers in Kathmandu have been infected with COVID-19 by the end of 2020.…”
Section: Introductionmentioning
confidence: 99%